THE INFLUENCE OF CREATIVE ECONOMICS ON HOUSEHOLD INCOME - Laurencia Primawati Degodona (The American Journal of Interdisciplinary Innovations and Research, 2024)
Research purposes As for the formula problems that arise from this research is how variable creation of new ideas and design product influential to enhancement income House ladder through creativity as intervening variable . Originality Subject from This research is the people of Medan City ( residents ) of Medan City, where The variables in this research are variables independent , that is role power health and social status , variables dependent , i.e variable well-being public as well as intervening variables are variables income . The results of the data analysis used using SEM analysis with using SMART PLS 4.0 software. As for technique data collection with questionnaire . Design/ methodology / approach Method study with use method descriptive quantitative data analysis using method structural equation model (SEM), where results process data with SEM method was carried out with PLS 4.0 application . Findings From results the research then the existing conclusion , namely partially variable discovery of new ideas and design influential products to enhancement income House ladder and influence to creativity . Simultaneously variable discovery of new ideas and design product influential to enhancement income House ladder through variable creativity public as intervening variable . Implementation The more increase discovery of new ideas, then the design process products for MSME businesses and homes hand become the more increase the ability to create and design new products , where increasing creativity will increase the ability of MSMEs to produce new products that meet expectations and desires consumers in order to boost and increase income No only for MSMEs, but also to increase business House ladder.